PEMILIHAN AREA PENGETAHUAN KUNCI PADA PROSES PRODUKSI BARANG CELUP LATEKS DENGAN PENDEKATAN LOGIKA FUZZY - Dedy Sugiarto; M Syamsul Ma’arif; Marimin Marimin; Illah Sailah; Sukardi Sukardi; Suharto Honggokusumo (JURNAL TEKNIK INDUSTRI, 2012)
One of important aspect in codification strategy in relation to knowledge management implementation is selective in choosing knowledge area to be codified. This paper showed a model for selecting key knowledge area using knowledge gap analysis and importance-performance matrix with fuzzy logic approach from latex dipped production process. Model was packaged in decision support system which designed using visual basic for applications and Matlab programming. Fuzzy average technique and Sugeno fuzzy inference system were used in this model. Four key knowledge areas detected based on two methods. They were compound formulation, product inspection and failure analysis, dispersion inspection and leaching.